Pendekatan dan Pengelolaan Delirium pada Pasien ICU: Deteksi, Intervensi Nonfarmakologi, dan Pencegahan Multikomponen - Ratno Samodro; Bowo Adiyanto; Erlangga Prasamya (Lembaga Pengembangan Kinerja Dosen, 2026)
Delirium is an acute neuropsychiatric syndrome characterized by fluctuating disturbances in attention, consciousness, and cognition, frequently observed in critically ill patients in the intensive care unit (ICU). This review aims to summarize current evidence on early detection methods, nonpharmacological interventions, and multicomponent prevention strategies for ICU delirium. The methodology involved a narrative literature review of studies published between 2012 and 2024, focusing on validated screening tools such as the Confusion Assessment Method for the ICU (CAM-ICU) and the Intensive Care Delirium Screening Checklist (ICDSC), their diagnostic performance, and implementation protocols. Findings indicate that daily screening with CAM-ICU (sensitivity 80%, specificity 96%) and ICDSC (sensitivity 74%, specificity 82%) facilitates timely identification. Nonpharmacological measures, including the ABCDEF bundle—encompassing pain management, spontaneous awakening and breathing trials, choice of sedation, delirium monitoring, early mobilization, and family engagement—have demonstrated efficacy in reducing delirium incidence and duration. Multicomponent prevention protocols such as the Hospital Elder Life Program (HELP) further decrease delirium risk through cognitive orientation, sleep promotion, and sensory support. Implications for practice include adopting standardized screening, embedding bundles into ICU workflows, and prioritizing environmental design modifications. Future research should explore optimized pharmacological adjuncts and cost-effectiveness analyses of bundle implementation.